Group work camp memories: Group power - Curiel, Herman F (Groupwork, 2017)
Abstract: Article describes how organizational history and early contact with two AASWG founders influenced author’s attendance at first 2009 group camp in USA. The collective camp experience is described in the context of Tuckman’s group development stages. Keywords:, Group Work Camp; stages of group development; groupwork history